The Effects of Bankruptcy on PT Megakarya Maju Sentosa, Ciputat, South Tangerang - Sri Siti Munalar; Basuki Rekso Wibowo; Zulkarnain Sitompul (Pelopor Publikasi Akademika, 2023)
Capital, which refers to cost, is one consideration in building low-cost apartment. Because of this developer can utilize the finance provided by banks. However, financing can be gained by selling the units before the low-cost apartment is built. This is as meant by Article 42 of the Law No. 20 of 2011 on low-cost apartment building, which allows the property units to be marketed before it is built (pre-project selling). However, before conducting the sales, there are some requirements to meet. This is contained in Article 43 of the Law No. 20 of 2011 on low-cost apartment building which states that the process of sale and purchase of unit before the unit is completely built can be conducted through Sale and Purchase Agreement (PPJB) made before a Notary. The PPJB stipulated by Paragraph 1 is executed after there are legal certainty over; a. landownership, b. ownership of building permit, c. the availability of facilities, infrastructures, and public utility, d. 20% (twenty per cent) minimally constructed, and the agreed terms. To manage the gained capital, it is necessary to correctly calculate everything in order to avoid bankruptcy. This research analyzes the effects of bankruptcy, which causes the auction on land and building. The issues discussed in this research are bankruptcy which leads to the auction of land and building assets, bankruptcy estate, and Limited Liability Company (PT)’s legal responsibility on its concurrent creditors. This research applies normative approach. The data were collected from documents or other references. They were analyzed qualitatively. The findings of this research show that the funds resulted from the auction was used to handle the auction fee, to pay both preferred and separatist creditors. Therefore, the concurrent creditors were not provided compensations as the results of the sold debtor’s assets. PT’s legal responsibility was to settle agreement only with the separatist creditors without involving concurrent creditors. Meanwhile, in building the low-cost apartment, concurrent also played great role to provide capital assistance by purchasing the unit of low-cost apartment. In fact, the settlement was only conducted with the separatist creditors. As a result, the concurrent creditors serve as the weakest party